2006
DOI: 10.1590/s1415-47572006000100002
|View full text |Cite
|
Sign up to set email alerts
|

Butyrylcholinesterase genetic variability in Guarani Amerindians from the Brazilian state of Mato Grosso do Sul

Abstract: Human butyrylcholinesterase (BChE; EC 3.1.1.8) is a polymorphic enzyme coded by the BCHE gene (3q26.1-q26.2) while the CHE2 gene (2q33-q35) determines a still not characterized substance that forms a complex with BChE (C 5 ), being the CHE2 C5+ and CHE2 C5-phenotypes detected in electrophoresis. The present study investigated BCHE and CHE2 variability and the BChE activity of Brazilian Guarani Amerindians from the Kaiowá and Ñandeva sub-groups living in several indigenous territories in the Brazilian state of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…The allele 539T (GCA>ACA; rs1803274) is known as the K allele. Furtado et al ( 2006) presented the hypothesis of the presence of this variant in the Native Americans, and our data supports that. For this same SNP, comparing the genotypic frequencies of the two Amerindian samples:Guarani‐Mbyá (GRC) and Guarani‐Ñandeva plus Guarani‐Kaiowá from Mato Grosso do Sul (GMS), a very significant difference was observed ( P < 0.001), further corroborating a closer similarity between Guarani–Ñandeva and Guarani–Kaiowá, whereas the Guarani–Mbyá is relatively more isolated (Furtado et al, 2006; Marrero et al, 2007; Tsuneto et al, 2003).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The allele 539T (GCA>ACA; rs1803274) is known as the K allele. Furtado et al ( 2006) presented the hypothesis of the presence of this variant in the Native Americans, and our data supports that. For this same SNP, comparing the genotypic frequencies of the two Amerindian samples:Guarani‐Mbyá (GRC) and Guarani‐Ñandeva plus Guarani‐Kaiowá from Mato Grosso do Sul (GMS), a very significant difference was observed ( P < 0.001), further corroborating a closer similarity between Guarani–Ñandeva and Guarani–Kaiowá, whereas the Guarani–Mbyá is relatively more isolated (Furtado et al, 2006; Marrero et al, 2007; Tsuneto et al, 2003).…”
Section: Resultssupporting
confidence: 89%
“…The few studies which examined the BCHE gene diversity in Amerindians suggest that some allelic variants were already present in Native Americans, but others are present due to recent gene flow with European, African, and Asian immigrants (Alcântara et al, 1995; Furtado et al, 2006; Nunes et al, 2008; Primo‐Parmo et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…The high A539T allele frequency in Table 1 (1 out of 3 individuals presents this allele) does not differ statistically (w 2 ) from those previously found for Southern Brazil (18.4 ± 2.8% in a sample with European ancestry and 17.1 ± 2.9% in a sample with European and African admixture) [19], North America (12.8 ± 3.4%) [20], Scotland (19.6 ± 3.9%) [21], Denmark (18.0 ± 5.4%) [22] and Japan (16.4 ± 2.4% [23]; 17.5 ± 2.3% [24]). This polymorphic allele with a worldwide distribution was also found in Amerindians from South America with lower frequencies than in other ethnic groups: Mapuche from Chile (5.76 ± 2.29%) [25] and Guarani from the Brazilian State of Mato Grosso do Sul (3.69 ± 0.85%) [26]. This variant, however, was not found in samples of Georgian (N = 86) and Ashkenazi (N = 30) Jews in which the atypical allele (D70G) was found with frequencies of 5.8 and 3.3%, respectively [27].…”
Section: Discussionmentioning
confidence: 67%
“…In 244 of these Amerindians, the 1615A variant of exon 4 (single nucleotide polymorphism -SNP, G/A: rs1803274; K variant; p.A539T) occurred with a frequency of 3.7% ± 0.9%, significantly lower than that found in Brazilians of European descent (18.4% ± 2.8%; Souza et al, 1998). The mean BChE activity was examined for 86 of these Amerindians and was found to be 4.01 ± 0.15 KU/L (Furtado et al, 2006), significantly lower than that for Brazilians of European descent but significantly higher than that for individuals from the Pacaás Novos, Sateré Mawé and Tenharim Brazilian Amerindian groups. Although the 1615A variant had previously been associated with lower BChE activity due to the decreased number of molecules (Rubinstein et al, 1978), Altamirano et al (2000) showed that the K and wild-type enzymes presented similar activity, protein turnover and tetramer formation.…”
mentioning
confidence: 93%
“…The distribution of BCHE gene variants has been investigated at the DNA level by Souza et al (1998) in two sample groups from Southern Brazil, one containing Brazilians of mainly European descent and the other containing Brazilians of mixed African and European descent, and by Furtado et al (2006) in Amerindian Brazilians, with the aim of contributing to a better understanding of both the evolution of the BCHE gene and of Brazilian population groups. Furtado et al (2006) investigated the BCHE gene variability in Guarani Amerindian Brazilians from the Kaiowá and Ñandeva groups from the Brazilian state of Mato Grosso do Sul. In 244 of these Amerindians, the 1615A variant of exon 4 (single nucleotide polymorphism -SNP, G/A: rs1803274; K variant; p.A539T) occurred with a frequency of 3.7% ± 0.9%, significantly lower than that found in Brazilians of European descent (18.4% ± 2.8%; Souza et al, 1998).…”
mentioning
confidence: 99%